2013
DOI: 10.1590/s0100-69912013000500012
|View full text |Cite
|
Sign up to set email alerts
|

Anastomose mecânica esofagogástrica cervical látero-lateral após esofagectomias

Abstract: Among the challenges of esophagectomies, the cervical anastomosis remains challenging for its consequences, the main being the anastomotic stricture. The authors present a technique for an Orringer-fashion mechanical cervical laterolateral esophagogastric anastomosis, which reduces the rate of fistula and stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…The fistula index (26%) found no difference between EMIL and ETHA and was similar to the literature (10-26%) 11 , 28 ; was lower in laparoscopy (20%), but without statistical significance. With mechanical laterolateral esophagogastric anastomosis 21 the rate of fistulas in the surgical service of the authors was reduced to 10-12% 7 ; the same has been demonstrated by other authors 10 , 21 , 25 .…”
Section: Discussionsupporting
confidence: 66%
“…The fistula index (26%) found no difference between EMIL and ETHA and was similar to the literature (10-26%) 11 , 28 ; was lower in laparoscopy (20%), but without statistical significance. With mechanical laterolateral esophagogastric anastomosis 21 the rate of fistulas in the surgical service of the authors was reduced to 10-12% 7 ; the same has been demonstrated by other authors 10 , 21 , 25 .…”
Section: Discussionsupporting
confidence: 66%